ENGINEERING GEOLOGICAL CHARACTERISATION OF BLOCK-IN-MATRIX ROCKS - Nikolaidis, G.; Saroglou, C. (Bulletin of the Geological Society of Greece, 2016)
Block-in-matrix rocks (“bimrocks”) are complex, mixed and heterogeneous formations of competent blocks embedded in weaker matrix. The inherent difficulty of sampling and consequently, laboratory testing of bimrocks leads to considerable challenging in geotechnical design and assessment of their engineering behaviour. An approach for the characterisation of “bimrocks” is the use of stereological analysis that extrapolates one-dimensional or two dimensional data to estimate the block volumetric proportion. This has been an established approach of dealing with bimrocks and melanges for the last two decades. This paper presents the parameters that are considered important for the engineering characterisation of such complex formations, while a case study from a bimrock in NW Greece is discussed.